A NUMERICAL AND EXPERIMENTAL STUDY OF UNSTEADY LOADING OF HIGH SOLIDITY VERTICAL AXIS WIND TURBINES - McLaren, Kevin W. (My University, 2011)
This thesis reports on a numerical and experimental investigation of the unsteady loading of high solidity vertical axis wind turbines (VAWTs). Two-dimensional, unsteady Reynolds averaged Navier-Stokes simulations of a small scale, high solidity, H-type Darrieus vertical axis wind turbine revealed the dominant effect of dynamic stall on the power production and vibration excitation of the turbine. Operation of the turbine at low blade speed ratios resulted in complex flow-blade interaction mechanisms. These include; dynamic stall resulting in large scale vortex production, vortex impingement on the source blade, and significant flow momentum extraction.
To validate the numerical model, a series of full-scale experimental wind tunnel tests were performed to determine the aerodynamic loading on the turbine airfoils, vibration response behaviour, and wake velocity. In order to accomplish this, a complex force measurement and wireless telemetry system was developed. During the course of this investigation, high vibration response of the turbine was observed. This resulted in conditions that made it difficult or impossible to measure the underlying aerodynamic loading. A vibration mitigation methodology was developed to remove the effect of vibration from the measured aerodynamic forces. In doing so, an accurate and complete measurement of the aerodynamic loading on the turbine blades was obtained.
Comparison of the two-dimensional numerical model results to the experimental measurements revealed a considerable over-prediction of the turbine aerodynamic force and power coefficients, and wake velocity. From this research, it was determined that the three-dimensional flow effects due to the finite aspect ratio of the turbine and blades, as well as parasitic losses, could be accounted for through the application of inlet velocity and turbine height correction factors. In doing so, the two-dimensional numerical model results could be properly scaled to represent the three-dimensional flow behaviour of the turbine prototype. Ultimately, a validated VAWT design tool was developed.
Keywords: Vertical Axis Wind Turbine; Dynamic Stall; Vibration Response; Three-dimensional Flow Effects; URANS Simulation; Vibration Mitigation Methodologies; Aerodynamics and Fluid Mechanics; Aerodynamics and Fluid Mechanics